Integrated Multi-Trophic Aquaculture (IMTA): Strategic model for sustainable mariculture in Samanco Bay, Peru - Loayza-Aguilar, Rómulo E.; Huamancondor-Paz, Yolanda P.; Saldaña-Rojas, Guillermo B.; Olivos-Ramirez, Gustavo E. (Frontiers in Marine Science, 2023)
The development of industrial mariculture in Peruvian coasts will continue to grow according to global trends; however, it is characterized by being mostly monospecific, resulting in ecosystemic impacts due to organic matter, which deteriorate the benthic system and encourage eutrophication, negatively affecting biodiversity and fishery resources, which in a long term could turn the activity into an unsustainable practice. Therefore, it is imperative to adopt new production models, focused on the sustainability principle, such as Integrated Multi-Trophic Aquaculture (IMTA), that allow for greater efficiency, competitiveness, and profitability, while guaranteeing environmental balance. In this context, the present study has addressed the problem of Argopecten purpuratus cultivation in Samanco Bay, in which, based on a diagnosis of the bay's conditions, details of the cultivation, and a thorough analysis of the IMTA concept, a strategic model for mariculture is proposed in order to be adopted by private companies, after a validation process. These concepts can be transferred for their adaptation to other scenarios. Furthermore, it is expected that the academic sector, private companies, and the competent authority will be able to intervene synergistically in this process.